GAS2-like 1 coordinates cell division through its association with end-binding proteins - Nazgiewicz, Alicja (Sci Rep, 2019)
Cell division involves the tightly coordinated rearrangement of actin and microtubules (MTs). We have previously shown that a member of the family of growth arrest-specific 2-like proteins, GAS2-like 1 (G2L1) regulates actin-MT crosstalk through its associations with plus-end microtubule tip-binding (EB) proteins. Here we show that G2L1 is involved in the regulation of cell division. We show that the depletion of G2L1 results in a reduction in the number of cells undergoing cell division and a significant proportion of those cells that do divide are either multinucleated, display deformed nuclei, or undergo cell division at a much slower rate. Exogenous expression of G2L1 mutants revealed that the association of G2L1 with EB1 is critical for regulated cell division and blocking this interaction inhibits cell division as observed in cells lacking G2L1. Taken together, our data suggest that G2L1 controls the precise regulation and successful progression of cell division through its binding to EB-proteins.